1989
DOI: 10.1525/aa.1989.91.1.02a00040
|View full text |Cite
|
Sign up to set email alerts
|

Hunting and Gathering in Tropical Rain Forest: Is It Possible?

Abstract: Hunters and gatherers living in tropical forests represent an important part of the total range of variation among contemporary hunting and gathering societies. Studies of tropical forest hunting and gathering peoples have contributed to our perceptions of the foraging way of life. Yet no peoples have ever been directly observed living independently of agriculture in tropical rain forest. This article tests the hypothesis that humans do not exist nor have ever existed independently of agriculture in tropical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
136
1
10

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(153 citation statements)
references
References 61 publications
2
136
1
10
Order By: Relevance
“…As recently as the 1980s and 1990s, anthropologists argued that tropical forests were unattractive environments for human occupation (e.g. 22 ). This view was further promoted by archaeologists, who, for example, saw tropical forests as barriers to the expansion of Late Pleistocene Homo sapiens foragers 23 , and also deemed them incapable of supporting agricultural populations 24 .…”
Section: Introductionmentioning
confidence: 99%
“…As recently as the 1980s and 1990s, anthropologists argued that tropical forests were unattractive environments for human occupation (e.g. 22 ). This view was further promoted by archaeologists, who, for example, saw tropical forests as barriers to the expansion of Late Pleistocene Homo sapiens foragers 23 , and also deemed them incapable of supporting agricultural populations 24 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies have shown that the divergence between ancestral pygmy populations and ancestral non-pygmy populations is quite ancient and occurred around 60 000 years ago. 2,3 Many evolutionary hypotheses have been proposed to explain this phenotype, 4 which could be due to an adaptation to food scarcity, 5 to the hot and humid climate of the rainforest, 6 to the density of this environment where mobility is uneasy, 7 to a life-history tradeoff in a context of high mortality 8,9 or to particular mate choices. 10 However, none of these hypotheses has proven to be true 4,11 and the evolution of the short stature of African pygmies remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Gamble, 1986). Not only would hunting game have been much harder in woodland (Bradley et al, 1989) but dispersal itself would have been particularly difficult in closed forest environments. Indeed, it is currently argued that most movement of human populations took place along the narrow open corridors provided by the floodplains of large rivers (Ashton et al,this issue,.…”
Section: Introductionmentioning
confidence: 99%